FEATURES OF COURSE MARTENSITE TRANSFORMATION IN STEEL AT HARDENING IN THE CONSTANT MAGNETIC FIELD - V.N. PUSTOWOIT; Y.V. DOLGACHEV (Advanced Engineering Research)
Using the method of electroresistance obtains data about course martensite transformations in steel under action of the magnetic field, formations specifying an opportunity stress-assisted martensite in temperature interval МS-МF in which superplasticity is shown. 208 Вестник ДГТУ, 2007. Т.7. №4(35)This opportunity is caused by magnetic heterogeneity austenite, presence in a paramagnetic matrix nanostrustural ensemble ferromagnetic ordering clusters which perceiving energy of an external magnetic field through magnetostrictive pressure, change fields of elastic forces in microvolumes of a nuclear lattice of a matrix, that causes to decrease in energy of formation germinal center of the critical size.